2007
DOI: 10.4140/tcp.n.2007.935
|View full text |Cite
|
Sign up to set email alerts
|

A Consultant Pharmacist's Role on a Geriatric Assessment Service

Abstract: The GAS program provided assistance to primary care providers caring for community-dwelling, at-risk seniors, resulting in improved pharmaceutical care, reduction in caregiver strain, and positive patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Four studies only reported outcomes for caregivers of patients that received comprehensive care and observed that caregivers were satisfied with the program [41,60], experienced an improved ability to cope with the disease of their family member, and experienced less anxiety and caregiver burden [42,60,62]. Although quality sum-scores of these studies were rather low, these studies' findings were rather consistent.…”
Section: Informal Caregiver Related Outcomesmentioning
confidence: 80%
See 2 more Smart Citations
“…Four studies only reported outcomes for caregivers of patients that received comprehensive care and observed that caregivers were satisfied with the program [41,60], experienced an improved ability to cope with the disease of their family member, and experienced less anxiety and caregiver burden [42,60,62]. Although quality sum-scores of these studies were rather low, these studies' findings were rather consistent.…”
Section: Informal Caregiver Related Outcomesmentioning
confidence: 80%
“…Three studies, however, observed that comprehensive care favored usual care in terms of medication compliance, medication appropriateness, antipsychotic and unnecessary drug use, detection of adverse drug reactions, and conditions with omitted drugs [40,70,71]. One study did not compare comprehensive care with usual care but also reported an improvement in medication management due to comprehensive care [62]. Considering the inconsistent findings across studies, there is insufficient evidence for a beneficial effect of comprehensive care on medication use.…”
Section: Functional Statusmentioning
confidence: 90%
See 1 more Smart Citation
“…Enhancing interdisciplinary team approach was the object of 24 studies [ 25 , 34 , 38 43 , 48 , 50 , 51 , 53 – 56 , 58 , 59 , 61 – 64 , 67 , 74 , 76 ]. Some of them highlighted the relevance of performing frequent team meetings [ 37 , 43 , 50 , 51 , 55 , 58 , 59 , 76 ]. One particular aspect was including the patient in the team [ 50 , 54 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Supporting the decision-making process and evidence-based practice were included in 19 studies [ 32 , 40 , 41 , 44 , 47 , 48 , 54 – 56 , 59 , 60 , 62 64 , 69 , 71 , 75 , 78 , 79 ]. The development, the integration and the use of clinical guidelines, algorithms and decision support tools were the most frequently cited element [ 32 , 40 , 41 , 44 , 47 , 48 , 54 – 56 , 59 , 60 , 62 64 , 69 , 71 , 78 , 79 , 81 ]. For example, in a study to evaluate the efficacy of a nurse-care management system designed to improve outcomes in patients with complicated cases of diabetes, Taylor et al (2003) specified that nurse-care managers used treatment algorithms developed by the Kaiser Permanente Medical panels based on national guidelines to titrate patient medications for diabetes, cholesterol, and hypertension [ 60 ].…”
Section: Resultsmentioning
confidence: 99%